(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The rapid integration of mobile devices into everyday life has created great opportunities to revise how high school students engage in technically complex subjects such as computer science. This work presents the design, algorithmic architecture, and empirical assessment of the Android mobile application (.apk), specially created to support the teaching of computer science in grades 5-9 in the general secondary education system of Uzbekistan. The application, based on the theory of Mobile Game-Based Learning (MGBL), uses the Room-SQLite relational database, a modular question bank system with Kotlin with Jetpack Compose to reflect the reactive interface, and a weighted evaluation algorithm, taking into account the complexity of the questions. The assimilation of the content of the quasi-experimental study conducted with the participation of 52 students of school No. 38 of the Gallaorol district of the Jizzakh region, divided into control and experimental groups, increased by 16 percent.